1981
DOI: 10.3382/ps.0600887
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Absorption of D-Galactose and L-Leucine and Intestinal Disaccharidase Activities in Growing Chickens Fed Different Raw Legume Diets

Abstract: A significant (P less than .01) impairment in the rate of growth, along with a significant (P less than .01) inhibition in the rate of in vivo intestinal absorption of D-galactose and L-leucine, and in the in vitro intestinal absorption of D-galactose, was found in growing chickens fed ad libitum over a 60-day period, diets containing the raw legumes Vicia faba, Glycine soja, Vicia ervilia, and Phaseolus vulgaris as the main source of protein. Furthermore, a significant (P less than .01) reduction in the intes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

1981
1981
1994
1994

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…Compared with the casein-fed animals, the rats fed the raw-legume diet displayed a reduction (P<.01) in rate of growth. The results agree with our previous observations (Bello et al, 1972;Santidrian 1981;Santidrian et al, 1981) and those of Ward et al (1977). Growth rate was not significantly altered by the addition of methionine to either the casein or the raw-legume diet.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Compared with the casein-fed animals, the rats fed the raw-legume diet displayed a reduction (P<.01) in rate of growth. The results agree with our previous observations (Bello et al, 1972;Santidrian 1981;Santidrian et al, 1981) and those of Ward et al (1977). Growth rate was not significantly altered by the addition of methionine to either the casein or the raw-legume diet.…”
Section: Resultssupporting
confidence: 93%
“…The mechanism by which raw field bean exerts its effects in growing rats remains unclear. The effect could be caused by substances present in the legume (Evans et al, 1973;Marquardt et al, 1977;Eggum, 1980;Liener, 1980), which might either alter the enterocyte membrane permeability or decrease the capacity of the carrier system for the substrate (Lasheras et al, 1980;Santidrian et al, 1981). Several investigators (Kakade and Evans, 1965;Jaffe and Vega, 1968)have indicated that impairment of the intestinal absorption process in animals fed raw legumes could result from association of the hemagglutinins contained in the legume (Marquardt et al, 1975) with epithelial cells.…”
Section: Resultsmentioning
confidence: 99%
“…In this connection, differences in the rate of absorption of galactose and leucine across the intestinal wall have been reported (Lasheras et al, 1980;Santidrian et al, 1981) ir. rats and chickens fed on diets containing different raw legume.…”
Section: Discussionmentioning
confidence: 92%
“…In concor dance with published evidence carried out in rats and chickens fed the same or other legume diets [6,7] a significant increase in liver and muscle proteolytic activity has been observed in the field bean-fed animals as compared to the casein-fed ones. The mechanism by which this catabolic effect takes place remains to be completely eluci dated although some hypotheses may be put forward: first, as mentioned above, a num ber of antinutritive factors contained in the raw seed [3,5,18] are known to produce a variety of physiological and biochemical ef fects; several investigators have postulated that some of these factors may interact and subsequently break down the lysosomal membrane, thus releasing the proteolytic en zymes into the cytoplasm [19]; on the other hand, we [20,21] and others [22] have dem onstrated that some factors contained in the raw legume seeds, especially tannins, cause an outstanding impairment of the capability of the intestinal epithelium to transport sug ars and amino acids in rats and birds: there fore, liver and muscle proteins begin to break down [23] in order to supply the body with the essential amino acids that cannot be absorbed through the intestinal tract. In fact, it is well known that protein and/or energy malnutrition brings about an increase in liver and muscle proteolytic activity [24], Finally, we have recently noted [25] that these catabolic catabolic effects on liver and muscle protein turnover are accompanied by a marked inhibition of the fractional protein synthesis rate, especially in skeletal muscula ture, this being an important complementary effect in order to explain, at least in part, the whole catabolic action of the raw field bean in growing animals.…”
Section: Discussionmentioning
confidence: 99%